The Influence of Food and Beverage Sub-Sector Manufacturing Companies Value on Financial Performance Listed Indonesia Stock Exchange - Hatuwe, Masna; Muspiha; Firman Gazali Djunaidi; Hamiru; Hayati Hehamahua (Institute for Research and Community Service, 2023)
This study aims to assess the effect of financial performance on the value of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2019-2021 period. The research method used is quantitative analysis with the analytical tool used is multiple linear regression. This research was conducted at food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange by accessing the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The results showed that partially profitability had a negative and insignificant effect on firm value, leverage had a negative and insignificant effect on firm value, liquidity had a positive and insignificant effect on firm value, while activity had a positive and significant effect on firm value. Simultaneously profitability, leverage, liquidity and activity simultaneously have a significant effect on the value of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange.